1978
DOI: 10.1378/chest.74.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory effects of flexible fiberoptic bronchoscopy in critically ill patients.

Abstract: The flexible fiberoptic bronchoscope is used increasingly often as a multipurpose instrument in critical care medicine. In poor risk patients who need continuous mechanical ventilation, rigid open tube bronchoscopy is a problem. With the flexible fiberoptic bronchoscope, however, diagnostic and therapeutic procedures can be carried out without interruption of ongoing mechanical ventilation. This procedure offers the possibility of bronchoscopy with reduced risk in debilitated patients. However, in these critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 13 publications
4
80
0
5
Order By: Relevance
“…In this series, a drop in SpO 2 >5% was observed in 65% of patients during FOB, with post-FOB SpO 2 values not significantly different from pre-FOB values. In a study by Lindholm et al [40], it was observed that gas exchange abnormalities slowly return to baseline after FOB and that PaO 2 values could decrease by about 40% if suctioning is applied during FOB. Krell [43] described that critically ill patients could experience a PaO 2 drop greater than the average 20 mm Hg observed in healthy subjects, with decreases of 30 to 60 mm Hg during FOB, and that hypoxemia may persist for several hours after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, a drop in SpO 2 >5% was observed in 65% of patients during FOB, with post-FOB SpO 2 values not significantly different from pre-FOB values. In a study by Lindholm et al [40], it was observed that gas exchange abnormalities slowly return to baseline after FOB and that PaO 2 values could decrease by about 40% if suctioning is applied during FOB. Krell [43] described that critically ill patients could experience a PaO 2 drop greater than the average 20 mm Hg observed in healthy subjects, with decreases of 30 to 60 mm Hg during FOB, and that hypoxemia may persist for several hours after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…They are often unstable and have failure of one or more organs. This could raise concern for the safety of FOB [4,40]. Bronchoscopy has demonstrated to be a safe procedure with a low rate of complications, even in training programs [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Serious cardiac adverse events, such as atrial and ventricular arrhythmias, myocardial ischemia, angina, and cardiac arrest are uncommon [3,5,30,[34][35][36]. They have been linked to sedation, hypoxemia [37], passage of the bronchoscope through the vocal cords [34], and pre-treatment with lidocaine anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible bronchoscope occupies 10% to 15% of a normal tracheal lumen 9 ; resulting hypoventilation may prompt a decrease in PaO 2 by 10 to 20 mm Hg. Procedures may also induce or exacerbate bronchospasm, 10 and, in the presence of hypoxemia, increase the risk of respiratory insufficiency or cardiac arrhythmias.…”
Section: Physiological Basis For Nppv-assisted Bronchoscopymentioning
confidence: 99%